Reproductive performance of buffalo cows (Bubalus bubalis) at small farms in Sukoharjo Regency, Central Java, Indonesia - Alifia, Murninur; Riyanto, Joko; Dewanti, Ratih; Cahyadi, Muhammad; Wati, Ari Kusuma; Pawestri, Wari; Yanti, Yuli (Universitas Sebelas Maret, 2023)
Objective: The buffalo population in Indonesia has generally increased in the last decade except in some regencies. This is because the farming activity is majorly dominated by smallholder farmers. Therefore, this study aims to obtain information about the reproductive performance of buffalo cows in small farms at Sukoharjo Regency, Central Java, Indonesia. It was conducted from April-September 2021 using a total of 33 respondents with 62 buffalo cows spread in Tawangsari, Sukoharjo, Mojolaban, Grogol, Baki, and Kartasura.Methods: The research method used is a survey method with the technique of determining the location and sampling used is purposive sampling. The materials used were buffalo farmers as respondents spread across 6 sub-districts. Mating system was natural mating. The data was collected from this sample include gestational age, age at first calving, service per conception (S/C), calving interval (CI) and post partum mating. The data obtained are then recorded and tabulated for the calculation of the average and standard deviation which is then presented as a percentage based on each parameter.Results: The results showed that the average length of gestation was 324.2±29.0 days, age at first calving 3.7±0.9 years, service per conception 1.1±0.4 times, calving interval 467.1±85.8 days, and post-partum mating was 128.5±69.3 days.Conclusions: It can be concluded that the reproductive performance of buffalo cows in smallholder farms at Sukoharjo Regency is relatively good.